Merck & Company, Inc. : the recall of Vioxx (A) - Gust, Andrew M.; Bartucci, Grant D.; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
Influenced by the preliminary results of an internal clinical trial, Raymond Gilmartin, CEO of Merck, announced that the company was pulling its blockbuster arthritis drug Vioxx from the worldwide market on September 30, 2004. Merck & Company, Inc., once the worlds largest pharmaceutical company, saw its stock price plummet 27% after the recall announcement. Facing recent sales declines, a barrage of lawsuits, and two separate government investigations, Merck is losing its once-stellar reputation in the pharmaceutical industry.
Originally published: Gust, A. M., Bartucci, G. D., & ORourke, J. S. (2005). Merck & Company, Inc.: The recall of Vioxx (A). 05-01 (A). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Merck & Co; Pharmaceutical industry -- Public relations; Product recall; Antiarthritic agents -- Testing